127k views
4 votes
Convert the function in standard form into vertex form. You must show your work. y = -x to the power of 2 + 2x + 3

1 Answer

4 votes

The given function is


y=-x^2+2x+3

We have to complete the square to find the vertex form. First, we move the independent term


\begin{gathered} -x^2+2x=-3 \\ x^2-2x=3 \end{gathered}

Then, we take the linear coefficient to divide it by 2 and elevate it to the square power


((2)/(2))^2=1^2=1

Then, we add this number on both sides


\begin{gathered} x^2-2x+1=3+1 \\ \end{gathered}

Now, we factor the trinomial.


(x-1)^2=4

Then, we move the power to the other side and we express it as a function.

Hence,


y=-(x-1)^2+4

User Viktiglemma
by
4.8k points